Hubungan Pelayanan Gizi, Kualitas Makanan, dan Konseling Terhadap Kepuasan Pasien di RSUD Balaraja - Fatkul Aliyah; Tri Ardianti Khasanah (Jurnal Kesehatan Indonesia, 2023)
Nutrition services as part of hospital services have a very important role that affecting patient confidence. The purpose of this research was to identify the association between the quality of nutrition service, food quality, and nutritional counseling toward patient satisfaction at Balaraja Hospital. This was analytical research with a cross-sectional design. The number of research samples was 122 subjects. Data were collected through questionnaires which included questions such as patient’s identity, quality of nutrition service, food quality, nutritional counseling, and patient satisfaction. The questionnaire was given in the form of questions and answers in the form of a Likert scale. Data analysis was done by using a statistical test using Chi-Square with the level of significance of ? = 0,05. The results of a statistical test to determine the relationship between the quality of service provided by officers (reliability) with patient satisfaction obtained a value of p = 0,001. The relationship between the service quality of officers (responsiveness) with patient satisfaction showed a value of p = 0,04. The relationship between the quality of service provided by officers (assurance) and patient satisfaction obtained a value of p = 0,001. Statistical test results to determine the relationship between food quality with patient satisfaction received a value of p = 0,004. The results of statistical tests were carried out to determine the relationship between nutritional consultation with patient satisfaction, obtaining a value of p = 0,007. There is a relationship between nutrition services, food quality, and nutritional counseling on patient satisfaction.